Estudo bioquímico, imunológico e farmacológico comparativo do fator de crescimento do nervo (NGF ) presente no veneno de Crotalus durissus cascavella Wagler, 1824 e na saliva de camundongo - Cunha, Geanne Matos de Andrade (1994)
The main objectives of the present work were to study, comparatively, the biochemical and immunological characteristics of the nerve growth factor ( NGF ) of snake venom ffom Crotalus durissus cascavella, a native species from the Brazilian northeast region, and of mice saliva. The pharmacological actions of the factor in experimental models of inflammation and pain, were also studied. Through Sephadex G-100 chromatography of the venom, a fraction was isolated which presented a molecular weight ( MW ) of 14,5-33 kD. Electrophoresis in SDS- polyacrylamide gel ( SDS-PAGE ) showed 4 bands in the region of 16,9-36,3 kD. In contrast, mice saliva after gel chromatography, a fraction was isolated which presented a MW of 26-44 kD and SDS-PAGE presented only 1 band in the region of 18,2-21,4 kD. The results from the immunodifiision test demonstrated that NGF immunoreactivity is presented in fractions of both snake venom and mice saliva , but they are not antigenically identical. The fractions promoted degranulation of mast cells from rat mesentery ( approximately 83% of cell degranulation/field at the dose of 100 /zg/ml). The NGF present in this fraction was responsible for the action, since it was inibited by anti-NGF. It was also shown that the fractions possess antiedematogenic activity in the mice paw edema test induced by carrageenan, in the dose of 1 /zg/kg with a 40 % inhibition of the edema. The fractions were not effective in causing inhibition of the edema produced by dextran. As the antiinflammatory action occurs at low doses, close to the physiological concentractions, it is possible that it could work as an endogenous antiinflammatory factor. In the writhing test in mice, the fractions from saliva ( 0,8 /zg/kg, s.c. ) and from venom ( 200 /zg/kg, s.c.) showed an antinociceptive action of approximately 80% and 50%, respectively. In the formalin test, the fractions from venom ( 200 /zg/kg, s.c. ) and from saliva ( 100 /zg/kg, s.c. ) showed an antinociceptive effect of 63% and 46% in the lst phase and 68% and 78% in the 2nd phase of the response, respectively. This action was not blocked by the opioid antagonist naloxone. The fractions were not effective in the Hot plate test in rats which is an indication that they possess a predominantly peripheral analgesic effect. The mechanism of action of NGF present in the fractions is not clear. It is possible that the factor acts at low doses through stabilization of membranes and/or desensitization of periferic nerve terminais through the inhibition of the release of nociceptive mediators such as Substance P.